HISTORY TEACHING IN THE FACE OF A NEW AND CHALLENGING HISTORICAL CONTEXT - Bezerra Cavalcanti, Genivaldo (Revista Gênero e Interdisciplinaridade, 2024)
The aim of this text is to discuss the use of information and communication technologies in the teaching and learning process in the subject of history. The topic was chosen as a result of the current technological scenario, which provides new configurations of social relations and allows for changes in various areas of people’s lives. Technology is currently embedded in all spaces and scenarios in society, and this is no different in the educational context. When used in the context of education, it allows for various possibilities of application, such as the use of digital media in classrooms, the implementation of virtual learning environments - in which it is possible to post content, lessons and interactions between teachers and students, as well as between students - in addition to countless other applications of technological resources, such as computers, tablets, among other tools. We also point out suggestions, possible paths, promoting reflection on teaching practice, in which teachers should need too adapt to new technologies.